World economic problems and policies - Prochnow, Herbert V. (New York : Harper & Row, 1965)
This volume undertakes to analyze thoughtfully a number of significant world economic problems and to assess realistically the policies that are being followed to solve these problems.
Includes bibliographical footnotes and index.
asm 22/01/2019
Loans
Keywords: Economic history; International economic relations; Economic policy